Quantitative Determination of Topiramate in Human Serum and Umbilical Cord Blood - Cifuentes, Cristina; Mennickent, Sigrid; De Diego, Marta (Current Pharmaceutical Analysis, 2019)
Background: Topiramate (TPM), an anticonvulsant drug, was determined in human serum and in umbilical cord blood. TPM can produce severe damage to the fetus (baby into mother´s uterus), and it is not always possible that epileptic women change their drug during pregnancy, because some antiepileptic drugs are not effective on some people. Using pregnant-mother serum blood, we can estimate drug levels in fetus serum, and by umbilical cord blood, is possible estimate drug levels in serum babies, without the ethic aspects to withdrawal blood of them. Methods: Quantitation was achieved by LC/DAD, using liquid-liquid extraction for isolation of TPM from both biological fluids, using dichloromethane as extraction solvent, and dabsyl chloride as derivatizing agent. Results: The method was linear over the concentration range of 5.0 to 20.0 μg/mL for TPM in human serum, and between 1.6-50.0 μg/mL for TPM in umbilical cord blood (r=0.999 and r= 0.998, respectively). RSD, for intra-assay study, was between 0.64%- 1.22% (n=3), and between 0.57% -1.86% (n=9) for inter-assay, when the biological fluid was human serum, and between 0.33% - 3.44%, and 3.38% -3.73%, respectively, when the matrix was umbilical cord blood. LOD was 0.40 μg/mL and 0.39 μg/mL for TPM in human serum and in umbilical cord, respectively, whereas LOQ was 1.20 μg/mL and 1.18 μg/mL, in each biological fluid. Recovery percentage for the accuracy study was between 94.0% and 109.8% (RSD ≤0.191). Conclusion: The method is precise, accurate, reproducible and selective for level analysis of TPM in both matrices.
Keywords: Topiramate